Is offshoring an International Process Only From Developed Countries to Emerging Economies? - Gião, Paulo Roberto; Júnior, Moacir de Miranda Oliveira (Internext, 2012)
The offshoring business is booming and what was used by few US pioneers are now spreading through the world (Economist Intelligent Unit, 2006). It is a very new issue at least regarding the origin of the expression and related to services and, even a common sense definition with a complete detailed explanation clarifying the cases is not available. Mol (2007), for instance, presents a variety of conceptual lens has been applied to outsourcing (and also can be applied to offshoring process): transaction cost economics, resource-based view, core competences, micro-economics, industrial organization, among others. From this list of perspectives, in this article we propose to analyze the applicability of transaction cost economics - TCE (Coase, 1937; Williamson, 1975, 1979) through its characteristic make-or-buy expression, considering the offshoring pace and emerging economy firms. The make-or-buy decision must be flexible enough to explain offshoring characteristics and developed and emerging economy firms scenarios. As secondary objectives, and to show the trail to the main purpose, two research questions were identified and discussed during the paper: Is offshoring process an international movement only from developed countries to emerging economies? Is the main reason of offshoring the looking for low-cost work / activities? To achieve the proposed objectives, the structure of this paper begins with a reasonable or acceptable definition of offshoring. Some reasons (or “the reason”) for the process are also another important starting point. The majority of articles referee the idea that low-cost is the main reason for offshoring, and if it is correct, transaction cost economics seems to be a good basis for our analysis purpose and integrative intention. Also some literature connections between offshoring and TCE are presented and, naturally TCE is presented in highlights for understanding these connections. Ending this section, some different arguments based on newer researches are presented by some authors presenting another perspective as the main reason.After this theoretical approach, a scenario analysis and some discussions are presented based on all possible interactions among firm from developed (DC) and emerging economies (EE) and examples of international corporations are presented to clarify and improve the understanding of our research questions and to build new contributions to international business theory. When analyzing all possible developed and emerging countries’ interactions, we argue that only looking for skills, capabilities, competences, etc., can be considered the main reason for offshoring to unify developed and emerging countries perspectives. Developed country firms have the additional benefit of low cost but considering the execution of same activities, so the same work (using similar skills, capabilities or competences) done with low cost. After all, final remarks are presented and some futures studies are proposed taking advantages of the pace of offshoring process.